Localized osmotic stress activates systemic responses to N limitation in Medicago truncatula–Sinorhizobium symbiotic plants - Martin, Marie-Laure; Pervent, Marjorie; Lambert, Ilana; Colella, Stefano; Tancelin, Mathilde; Severac, Dany; Clément, Gilles; Tillard, Pascal; Frugier, Florian; Lepetit, Marc (Frontiers in Plant Science, 2023)
The topic of this paper is the physiological adaptation of legume-rhizobium symbiotic plants to fluctuating and heterogeneous environmental constraints. How inter-organ signaling may contribute to whole plant adaptation to a localized stress is the major biological question addressed by this study using molecular and physiological approaches. The response of Medicago truncatula/Sinorhizobium medicae symbiotic plants supplied exclusively by symbiotic nitrogen fixation to a localized water constraint was analyzed using split-root systems. Results argue for a role of systemic N signaling in the root compensation of local variations impairing locally the symbiotic activity.